Factors Affecting Uncertainty in Women with High-Risk Pregnancies. Issue 6 (November 2019) - Schmuke, Ashley D.
Abstract: Objective: To evaluate the state of the science on uncertainty in high-risk pregnancy and identify factors that influence uncertainty in women diagnosed with a high-risk pregnancy. Data Sources: Primary research articles from CINAHL, Ovid, MEDLINE, Scopus, and PsycINFO written in English, without date restrictions. Study Selection: Nineteen articles were identified, including 14 qualitative studies and 5 quantitative studies. Data Extraction: This integrative review was guided by Whittemore and Knafl's methodology. Studies were graded on level and quality of evidence as per Dearholt, Dang, and Sigma Theta Tau International. Data Synthesis: Studies were synthesized by using constant comparative methods according to factors influencing, outcomes of, and management of uncertainty. Conclusion: Uncertainty is a prominent theme in women experiencing a high-risk pregnancy. Uncertainty is influenced by various personal, pregnancy-related, demographic, and healthcare-related factors. Findings may offer insight and empathy for healthcare professionals. Nurses who understand significance of uncertainty in adjusting to two conflicting life events have the opportunity to help women in their understanding of a high-risk diagnosis during pregnancy through anticipatory guidance. Future research is needed to explore factors affecting uncertainty and to understand the experience of high-risk pregnancy to develop interventions aimed at mitigating uncertainty in high-risk pregnant women. Abstract : In this integrative review, women's uncertainty in high risk pregnancy is explored. Uncertainty is influenced by various personal, pregnancy-related, demographic, and health care-related factors. Nurses who appreciate the significance of uncertainty during pregnancy have the opportunity to help women in their understanding of a high-risk diagnosis during pregnancy through anticipatory guidance.